Changing mindsets in the modern foreign languages classroom: an intervention combining intelligence theories and reading strategies. Issue 5 (2nd September 2020) - Molway, Laura; Mutton, Trevor
ABSTRACT: Recent research has established that it is academically advantageous for students to adopt an incremental view of their intelligence and that this is a key marker of a student's level of self-efficacy. The self-efficacy of students following Modern Foreign Languages (MFL) courses in UK secondary schools is known to be low. Interventions have been successful in modifying students' intelligence theories in the short term, but less research has been conducted into the longer-term impact of such interventions. This paper investigates the impact of intervention training focussed on the benefits of adopting both an incremental theory of intelligence and a strategic approach to learning. We report the results of a year-long intervention study with a quasi-experimental design based in a large comprehensive secondary school in England. The participants were five Year 9 German as a foreign language classes ( N  = 127). The impact of two interventions is assessed through in-depth questionnaires, analysis of student outcomes, and students' intentions to continue with post-compulsory language study. The findings of this study yield significant implications for teachers' classroom practice. Targeted intervention is shown to have a lasting impact on students' theories of intelligence. The combination of interventions appears to have had an effect on the frequency with which students report adaptive attributions for failure. Most strikingly, for students of lower initial attainment, such interventions may have the power to transform attainment and motivation to continue with language study.